Lirismo verbal e virtual: travessia de sentidos - Paiva, Natascha Gomes (2009)
The investigation subject of this dissertation is the configuration of erotic verbal lyrism and erotic virtual lyrism based on reflection sonnets by Florbela Espanca (1894 1930) and digital verses/poems by Rui Torres (1973). The sonnets were selected from Poemas Florbela Espanca, by Florbela Espanca and organization by Maria Lúcia Dal Farra and the digital verses/poems Amor-mundo, ou a vida, esse sonho triste from the electronic address www.telepoesis.net, by Rui Torres. Our purpose is to analyses the lyrism produced by both authors, indicating likeness and differences that the two lyrical forms manifests. The research problem-question was: is there a fusion between erotic verbal lyrism produced by Florbela Espanca and the erotic virtual lyrism produced by Rui Torres ? Or even better, assume that Florbela s poetry produces a erotic lyrical voice, and the Rui Torre s poetry, a virtual lyrical voice, we can tell that Torre s poetry dialogues with the Florbela s eroticism ? To conduct the investigation were selected the hypothesis: Rui Torres make use of in a virtual way, in his poems, poetics procedures from erotic verbal lyrism florbeliano, developing a dialogue with Florbela Espanca poetry; Rui Torres, in the moment he establish a fusion between his lyrism and Florbela s, extended the florbeliano lyrism and reveal lyrical potency from the virtual environment. The critic and theorist are based on the specialist studies from the portuguese poet, like Maria Lúcia Dal Farra, erotic and poetic studies by Georges Bataille and Octavio Paz, researches from the literary and digital environment like Lúcia Santaella and Joan Campás. Among conclusions, stand out that sensuality, in both poets, is metaphorically represented, impelling the course from the erotic voice. The poetic speech manifests advocate of the representation and fruition from desire and pleasure